Pharmacognostic study and antioxidant capacity of the Smilax purhampuy Ruiz species that grows in Ecuador - Pilar A. Soledispa Cañarte; Raisa Mangas Marín; Viviana García Mir; Migdalia Miranda Martínez; Carolina F. Matute Jimbo; Arlu I. Tello Mayorga (GarVal Editorial Ltda., 2022)
Context: Smilax purhampuy Ruiz (sarsaparilla) is traditionally used to treat various ailments such as sudorific, diuretic, purifying, hypoglycemic, arthritis, dermatological infections, intestinal, stomach and prostate inflammations, vaginitis and viral diseases. However, the investigations that justify the use of this species are scarce. Aims: To evaluate pharmacognostically and chemically leaves and rhizomes of sarsaparilla, and their antioxidant capacity. Methods: The pharmacognostic analysis of both plant organs was carried out from the determination of their physicochemical parameters, the phytochemical screening, the quantification of phenols and total flavonoids and the evaluation of the antioxidant capacity by three in vitro methods (FRAP, DPPH and ABTS). Results: The leaves and rhizomes of the species showed a similar chemical composition, although some metabolites seem to be found at different concentrations. Although the two organs studied presented antioxidant activity, it was higher in the leaves, which could be associated with the higher content of phenols and flavonoids. Conclusions: The results obtained made it possible to report the quality parameters for the first time and suggest the chemical composition of both organs, showing some differences between them. The evaluation of the antioxidant capacity demonstrated the potential of the species to be used as a natural remedy.